Dopamine release in the nucleus accumbens is altered following traumatic brain injury. (21st April 2017) - Chen, Yuan-Hao; Huang, Eagle Yi-Kung; Kuo, Tung-Tai; Hoffer, Barry J.; Miller, Jonathan; Chou, Yu-Ching; Chiang, Yung-Hsiao
Highlights: TBI was associated with changes in DA transmission in both the core and shell of NAC, with greater changes in the core. These alterations were correlated with severity of injury, becoming most severe 1–2 weeks after injury. The data suggest the NAC core and striatum may subserve parallel functions, whereas the shell is distinct. These electrochemistry data may help explain affective and cognitive changes respond to TBI. Abstract: Mild-to-severe traumatic brain injury (TBI) is frequently associated with prolonged dysfunction of reward circuitry, including motivation and salience, which suggests alterations of dopamine (DA) processing within the core and shell of the nucleus accumbens (NAC). Using fast-scan cyclic voltammetry in a rodent model of traumatic brain injury, we found that stimulus-evoked DA release is distinct in the core and shell of the NAC, with the shell being less responsive to tonic stimulation and more sensitive to the number of pulses when phasic stimulation is applied. Exposure to TBI was associated with major changes in both release and reuptake of DA in both the core and shell of NAC, with greater changes seen in the core. These alterations evolved over time, becoming most severe 1–2 weeks after injury with subsequent recovery, and the extent and progression of these abnormalities was correlated with severity of injury. Taken together, these data support behavior and anatomical studies suggesting the NAC core and striatum may subserve parallel functions, whereas the shell is distinct. These data offer a unique window on how different neurological systems respond to TBI and may help explain affective and cognitive changes that are seen.